Simple one pot synthesis of nano gold-mesoporous silica and its oxidation catalysis - Sekhar, A. C. Sunil; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Today, 2012)
A simple one pot synthesis strategy using a non ionic triblock copolymer P123 as reducing as well as templating agent has been employed to prepare nano gold particles incorporated in the pores of mesoporous silica catalyst. The catalyst is characterized by XRD, nitrogen adsorption desorption isotherms at 77 K and TEM. The presence of small gold nanopartilces (similar to 2-4 nm) clearly demonstrated that this strategy can be effective in incorporating Au inside mesochannels. The catalyst reduced at 300 degrees C in H-2 was found to be active for oxidation reactions, such as CO oxidation, and benzyl alcohol. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Alcohol oxidation; CO oxidation; Gold catalysis; Mesoporous silica

Metal-mediated alkynediol cycloisomerization: first and second generation formal total syntheses of didemniserinolipid B - Das, Shyamsundar; Induvadana, Boddeti; Ramana, C. V. (Tetrahedron, 2013)
A formal total synthesis of didemniserinolipid B was developed by employing a regioselective metal-mediated 6-endo-dig alkynol-cycloisomerization reaction. Two routes for the synthesis of key Burke's intermediate have been developed. Our initial approach involved the introduction of a C-17-allcynol followed by Pd-mediated cycloisomerization and then coupling with the serinol unit prior to the introduction of an alpha,beta-unsaturated ester unit through selective oxidation of 1 degrees-OH followed by a two-carbon Wittig homologation. Alternatively, the second generation strategy featuring the serinol coupling with the C-17-alkynol followed by alkyne addition to the epoxide and subsequent Au-mediated cycloisomerization of an acetonide protected alkynediol unit has been executed. This approach has avoided several late stage protection-deprotection events. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Alkynol-cycloisomerization; Bicyclic ketal; Gold catalysis; Palladium catalysis; Zipper reaction

Synthesis of C-disaccharides through a one-pot alkynol cycloisomerization-reductive deoxygenation - Narute, Sachin B.; Rout, Jeetendra Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2013)
Keywords: C-disaccharides; carbohydrates; Epoxide-alkyne coupling; Gold catalysis; Reductive deoxygenation

Total synthesis of naturally occurring cephalosporolides E/F - Kona, Chandrababu Naidu; Ramana, C. V. (Tetrahedron, 2014)
A modular total synthesis of cephalosporolides E/F featuring sequential epoxide-alkyne coupling and subsequent highly regioselective gold catalyzed alkynolcycloisomerizatio of the resulting alkynetetrol to construct the central spiroketal core has been documented. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Alkynetetrol; Cephalosporolide; Epoxide-alkyne coupling; Gold catalysis; Spiroketalization

Oxidation catalysis by large trisoctahedral gold nanoparticles: Mind the step! - Sreedhala, S.; Sudheeshkumar, V.; Vinod, C. P. (Catalysis Today, 2015)
To understand the origin of catalysis by gold and to probe the role of defects and interfaces, benchmark reactions namely CO oxidation and benzyl alcohol oxidation were carried out on supported trisoctahedral gold nanoparticles and on the inverse catalyst system. The sizes of these particles which are between 45 nm and 110 nm, are well beyond the quantum size regime and well above the optimum size range where gold is considered to be catalytically active. The periodic steps sites in contact with oxide support interface were able to promote the reaction. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: CO oxidation; Defects; Gold catalysis; Inverse catalysta; Steps and kinks

Synthesis of Au@Ni bimetallic core shell nanoparticle and nanochains in soyabean oil and their catalytic hydrogenation reactions - Bharathan, Vysakh A.; Yadukiran, V.; Lazar, Anish; Singh, Anand. P.; Vinod, Chathakudath P. (ChemistrySelect, 2016)
Synthesis of Au@Ni bimetallic core shell nanostructures using commercially available soya bean oil as the solvent through a sequential reduction strategy is reported. The energy efficiency and economic viability comes from the much milder temperatures and replacement of expensive and environmentally hazardous solvents like long chain organic amines and acids previously reported for synthesis. Thus, core shell nanoparticles having size regime of 10-15 nm with an excellent control over the nickel shell thickness (2 nm) over the gold core (8-10 nm) and Au@Ni nanochains is achieved. The synthesized materials are demonstrated to synergistically catalyze hydrogenation of nitro and C-C multiple bonds with much better efficiency as compared to individual nanoparticle counterparts.
Keywords: Bimetallic nanoparticles; Gold catalysis; hydrogenation reactions; synergistic effects

Ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox relay catalysis - Sancheti, Shashank P.; Akram, Manjur O.; Roy, Rupam; Bedi, Vaibhav; Kundu, Shubhankar; Patil, Nitin T. (Chemistry-An Asian Journal, 2019)
Reported herein is an ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox catalysis to access highly functionalized 2-(2-hydroxyaryl)-2-alkoxy-1-arylethan-1-ones. Detailed mechanistic studies suggested a relay process, initiating with gold-catalyzed hydroalkoxylation of alkynes, to generate enol-ether followed by a key formal [4+2]-cycloaddition reaction. The successful application of the present methodology was also shown for the synthesis of benzofurans.
Keywords: binary catalyst system; Gold catalysis; organocatalyst; photoredox; synthetic methodology

Competing intra- vs intermolecular nitrene transfer in the [Au]-catalysed reaction of 2-alkynylphenylazides - Dhote, Pawan S.; Ramana, V. Chepuri (Advanced Synthesis & Catalysis, 2022)
The possibility of interrupting the gold-catalysed intramolecular cyclization of 2-alkynylphenylazide derivatives, employing known nitrene transfer reagents such as anthranil and its isomer 1,2-benzisoxazole, has been attempted in search of developing simple tools for product diversification. With 1,2-benzisoxazoles, the intermolecular nitrene transfer leading to quinazoline is competitive with intramolecular azidoalkyne cyclization resulting in spiro indol-3-ylidene derivatives. However, in case of the reaction in the presence of anthranil, both intra- and intermolecular nitrene transfer processes result in the same product indol-3-ylidene.
Keywords: 2-Benzisoxazole; Anthranil and 1; Gold catalysis; Nitrene Transfer; Quinazoline

Attempted synthesis of the central 2,2-disubstituted pseudoindoxyl core of Austamide via a [Au]-catalyzed nitroalkyne cycloisomerization and intramolecular [3+2]-cycloaddition - Halnor, Swapnil V.; Ramana, Chepuri V. (Tetrahedron, 2024)
Herein, we describe an Au-catalyzed cycloisomerization process of a nitroalkyne that was projected to construct the central 2,2-disubstituted pseudoindoxyl core of the natural product Austamide. Our intended strategy for forging the pseudoindoxyl core is based on the nitroalkyne cycloisomerization followed by a subsequent intramolecular [3 + 2] cycloaddition. However, the [3 + 2] cycloaddition occurred in an undesired manner, ultimately leading to a complex hexacyclic scaffold.
Keywords: Austamide; Gold catalysis; Intramolecular [3+2] cycloaddition; Nitroalkyne cycloisomerization